‘We became refuse and rubbish’: Violence, filth, and rehumanization after exile - Lemos, T. M. (Journal for the study of the Old Testament, 2025)
While frameworks of purity and impurity were widespread in ancient West Asia and well known before the exile, many exilic and postexilic sources focalize purity concerns. This article will explore the connection between ancient West Asian texts associating or equating conquered groups with filth and disgust-eliciting substances and the focus on impurity-removal that is so obtrusive in post-exilic biblical sources. I will argue that the rituals of purification detailed in the priestly texts of the Pentateuch constituted practices of rehumanization, seeking to alleviate the deep-seated sense of filth and impurity that a variety of texts from the exilic and post-exilic eras so clearly exhibit. These priestly texts arguably offered to Judeans both purification and a path to healing from the dehumanizing violence suffered by earlier generations, violence leaving after-effects still felt by postexilic communities, as various early postexilic texts demonstrate.